Glycemic excursion minimization in the management of type 2 diabetes: a novel intervention tested in a randomized clinical trial. Issue 2 (16th December 2020) - Cox, Daniel J; Banton, Tom; Moncrief, Matthew; Conaway, Mark; Diamond, Anne; Holmes, Viola; Green Pastors, Joyce; Wolf, Anne; Fang, Kun; McCall, Anthony
Abstract : Introduction: This study of adults with type 2 diabetes employed a non-inferiority hypothesis to investigate whether an innovative lifestyle focused on minimizing postnutrient blood glucose (BG) excursions (glycemic excursion minimization (GEM)) would be equivalent or superior to conventional weight loss (WL) therapy in regard to reducing HbA1c, and superior to WL when investigating physical, behavioral and psychological secondary outcomes. The impact of BG feedback on GEM efficacy was also investigated. Research design and methods: 178 adults with type 2 diabetes for ≤10 years, HbA1c ≥6.8%, and not using insulin were randomized to WL (n=40) or one of three versions of GEM. Didactic (GEM-D, n=39) taught participants to choose low-glycemic load foods, reduce sedentary time and increase moderate routine physical activity. GEM-S (n=51) received GEM-D and systematically measured BG before and after meals and physical activity to educate and motivate food and activity choices. GEM-C (n=48) received GEM-D with continuous glucose monitoring feedback. All participants received 6 hours of group training and BG and activity monitors. Before and 3 months after treatment, participants were assessed for HbA1c, lipids, weight, routine physical activity, nutrition, depression, diabetes empowerment and distress. Results: GEM versions did not differ in primary or secondary outcomes, so they were combined for analyses. While WL reduced body mass index (BMI) (p=0.005), GEM demonstrated a greater reduction in HbA1c (p=0.005), BMI (p=0.013), carbohydrate intake (p=0.001), BG response to a glucose challenge (p=0.02), and cardiovascular risk (p=0.003). Only GEM participants significantly improved diabetes empowerment, diabetes distress, depressive symptoms, steps/day, and active hours and reduced calories/day. Neither intervention had negative side effects. Conclusions: GEM is an effective alternative to WL with respect to physical, behavioral and psychosocial outcomes. Trial registration number: NCT03196895 .